2020
DOI: 10.1097/mpa.0000000000001485
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent FOXM1 Promotes Epithelial-to-Mesenchymal Transition Via Cellular Metabolism and Targeting Snail in Human Pancreatic Cancer

Abstract: Objectives Transcription factor Forkhead box protein M1 (FOXM1) plays critical roles in the progression of cancer including epithelial-to-mesenchymal transition (EMT). The aim of this study is to characterize the regulatory mechanisms of FOXM1 in EMT via pancreatic cancer metabolism. Methods We investigated the regulation of EMT via mitochondrial respiration by FOXM1 using pancreatic cancer cell lines HPAC and PANC-1 and normal human pancreatic duct epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…On the contrary, PANC‐1 spheroids showed a lower invasive behavior: higher growth in area is evident, but individual cells did not leave spheroid in none of examined conditions. Probably, this is due to a limited chemotactic stimulus and a low concentration of glucose, 65 that was used as chemoattractant. In fact, it is known that high glucose concentration, after about 48 h, is expected to induce epithelial‐mesenchymal transition (EMT) in epithelial cell lines, by which cells lose epithelial cell–cell adhesion with improved tendency to move through extracellular matrix 66 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…On the contrary, PANC‐1 spheroids showed a lower invasive behavior: higher growth in area is evident, but individual cells did not leave spheroid in none of examined conditions. Probably, this is due to a limited chemotactic stimulus and a low concentration of glucose, 65 that was used as chemoattractant. In fact, it is known that high glucose concentration, after about 48 h, is expected to induce epithelial‐mesenchymal transition (EMT) in epithelial cell lines, by which cells lose epithelial cell–cell adhesion with improved tendency to move through extracellular matrix 66 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, a proteomics study of the breast cancer cell line MCF-7 revealed that FOXM1 altered the expression of 37 proteins associated with mitochondrial biogenesis and glycolysis [ 294 ]. In pancreatic cancer, FOXM1 expression was upregulated in a glucose-dependent manner, which correlated with epithelial-to-mesenchymal transition (EMT) in pancreatic cancer cell lines [ 310 ]. In addition, downregulation of FOXM1 induced pancreatic cancer cells to use mitochondrial respiration rather than aerobic glycolysis in high-glucose medium, further linking FOXM1 to the glycolytic pathway [ 310 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…In pancreatic cancer, FOXM1 expression was upregulated in a glucose-dependent manner, which correlated with epithelial-to-mesenchymal transition (EMT) in pancreatic cancer cell lines [ 310 ]. In addition, downregulation of FOXM1 induced pancreatic cancer cells to use mitochondrial respiration rather than aerobic glycolysis in high-glucose medium, further linking FOXM1 to the glycolytic pathway [ 310 ]. Similarly, FOXM1 knockdown decreased glucose utilization, lactate production, and lactate dehydrogenase (LDH) activity in several pancreatic cell lines and downregulated phosphoglycerate kinase 1 (PGK-1) and lactate dehydrogenase A (LDHA) [ 311 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…Compared with small molecule PROTACs, the design and synthesis of p-PROTACs is simpler, and possess the ability to target “undruggable” targets with high specificity and low toxicity, and can resist to mutation targets. Since GLUT1 levels can correlate with response to FOXM1, there is increasing interest in understanding cell proliferation and glycolysis [ 42 , 43 ]. However, while PD-L1 regulation has been extensively studied in cancer cells, the specific link between PD-L1 and FOXM1 has received less attention.…”
Section: Discussionmentioning
confidence: 99%